Antigenic typing of brazilian rabies virus samples isolated from animals and humans, 1989-2000 - Silvana Regina FAVORETTO; Maria Luiza CARRIERI; Elenice Maria S. CUNHA; Elizabeth A.C. AGUIAR; Luzia Helena Q. SILVA; Miriam M. SODRÉ; Maria Conceição A.M. SOUZA; Ivanete KOTAIT (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
Animal and human rabies samples isolated between 1989 and 2000 were typified by means of a monoclonal antibody panel against the viral nucleoprotein. The panel had been previously established to study the molecular epidemiology of rabies virus in the Americas. Samples were isolated in the Diagnostic Laboratory of the Pasteur Institute and in other rabies diagnostic centers in Brazil. In addition to the fixed virus samples CVS-31/96-IP, preserved in mouse brain, and PV-BHK/97, preserved in cell culture, a total of 330 rabies virus samples were isolated from dogs, cats, cattle, horses, bats, sheep, goat, swine, foxes, marmosets, coati and humans. Six antigenic variants that were compatible with the pre-established monoclonal antibodies panel were defined: numbers 2 (dog), 3 (Desmodus rotundus), 4 (Tadarida brasiliensis), 5 (vampire bat from Venezuela), 6 (Lasiurus cinereus) and Lab (reacted to all used antibodies). Six unknown profiles, not compatible with the panel, were also found. Samples isolated from insectivore bats showed the greatest variability and the most commonly isolated variant was variant-3 (Desmodus rotundus). These findings may be related to the existence of multiple independent transmission cycles, involving different bat species.